Snapshot of South African Salmonella: development of a sensitive tool to investigate the distribution of Salmonella Enteritidis clades in 2012 and 2013 - Gallichan, Sarah (My University, 2020)
Salmonella Enteritidis is the most commonly reported non-typhoidal Salmonella serovar causing human disease, and is implicated in both gastroenteritis and invasive non-typhoidal Salmonella disease worldwide. Whole-genome sequence (WGS) comparison of Salmonella Enteritidis isolates from across the world identified four definitive clades: Outlier, Global, East African and West African. Three of these clades were implicated in epidemics: the Global Clade was linked to poultry-associated gastroenteritis, while the two African clades were related to invasive disease. Despite the recognition of different Salmonella Enteritidis clades, the distribution and epidemiology of these clades across Africa is poorly understood. To investigate this, we developed a sensitive real-time PCR assay that was capable of differentiating between the Salmonella Enteritidis clades. This assay was then used to investigate 618 Salmonella Enteritidis isolates originating from four South African provinces over a period of two years (2012 – 2013). Associations between particular clades and province, antimicrobial resistance and HIV status were explored using statistical analysis. Majority of the South African isolates were classified within the Outlier clade (61.00%), with fewer classified within the Global clade (38.83%) and only one isolate classified within the West African Clade (0.16%). Of note, the isolates within the Global clade were strongly associated with decreased ciprofloxacin susceptibility (37/240, 15.42%, OR: 7.45, CI: 3.526 – 15.751) and invasive disease (140/240, 58.33%, OR: 1.57, CI: 1.13 – 2.17). Thus, we have highlighted the importance of monitoring Salmonella Enteritidis clades in sub-Saharan Africa in order to gain a better understanding of the distribution and epidemiology. The development of a sensitive realtime PCR assay provides a cost-effective alternative to WGS for use in resource-limited settings.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020